Peningkatan Kepercayaan Diri Siswa Kelas III A Melalui Penerapan Metode Storytelling Berbantuan Media Foto Keluarga dalam Pembelajaran IPAS di SDN Keleyan 2 - Sielvia Dwi Kumalasari; Oktafia Fitriani; Siti Arofah; Lina Safira; Syarifah; Tyasmiarni Citrawati (Insan Cendekia : Jurnal Pendidikan dan Kebudayaan, 2026)
This Classroom Action Research was conducted in class III A of SDN Keleyan 2 with the aim of improving students’ self-confidence in the IPAS subject through the application of the storytelling method assisted by family photo media. The problem found in the previous learning process was the low level of students’ self-confidence, which was indicated by the lack of courage to appear in front of the class, answer questions, and tell their family traditions. This research was carried out in two cycles, each consisting of planning, implementation of actions, observation, and reflection. The research subjects consisted of 21 students, including 9 female students and 12 male students. Data were collected through observation, attitude questionnaires, and documentation. The results showed an increase in students’ self-confidence from cycle I to cycle II, which was marked by an increase in students’ courage in expressing opinions, telling stories in front of the class, and actively participating in learning. Furthermore, the classical completeness target of 70% was successfully achieved in cycle II. The application of the storytelling method through family photo media was carried out gradually, starting from paired storytelling activities to independent presentations, accompanied by positive reinforcement from the teacher. Thus, it can be concluded that the storytelling method assisted by family photo media is effective in improving students’ self-confidence and supporting more active and meaningful IPAS learning.